2014
DOI: 10.1002/jbm.a.35148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of titanium-based nanotube films on osteoblast behaviorin vitro

Abstract: One of the major research interests of nanomedicine is the designing of harmless and biocompatible medical devices. To improve the features of Ti surface, TiO2 based nanotube (TNT) films (50 nm diameter) achieved by anodic oxidation and thermal treatment were grown on titanium and on Ti6Al4V and Ti6Al7Nb alloys. Their in vitro toxicity and biocompatibility were investigated using G292 osteoblast cell line. The LDH release after 24 and 48 h of exposure demonstrated that TNT layers were not cytotoxic. The cell g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 21 publications
(41 reference statements)
4
10
1
Order By: Relevance
“…In a recent study, Stan et al suggested that NTs on Ti6Al4V alloy enhanced G292 osteoblast cell growth when compared to anodized Ti6Al7Nb alloy [41]. Likewise, in another study, Saharudin et al suggested that NTs on Ti6Al4V alloy increased PA6 cell adhesion and viability when compared to the non-anodized material [42].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, Stan et al suggested that NTs on Ti6Al4V alloy enhanced G292 osteoblast cell growth when compared to anodized Ti6Al7Nb alloy [41]. Likewise, in another study, Saharudin et al suggested that NTs on Ti6Al4V alloy increased PA6 cell adhesion and viability when compared to the non-anodized material [42].…”
Section: Discussionmentioning
confidence: 99%
“…The ratio between the amount of nuclear GSH and cytoplasmic GSH provides valuable information regarding the proliferative status of the cells grown on different surfaces [24]. As shown in Fig.…”
Section: In Vitro Response Of Human Osteoblastsmentioning
confidence: 99%
“…After 24 h of cultivation on TiO 2 , TiO 2 /HA and TiO 2 / MWCNT-COOH/HA samples, the intracellular GSH was labeled and quantified as it was previously described [24]. Briefly, the cells were incubated with 5 mM CellTracker Green 5-chloromethylfluorescein diacetate (CMFDA; Molecular Probes from Invitrogen) for 30 min at 37 1C in a humidified atmosphere with 5% CO 2 .…”
Section: Gsh Labeling and Fluorescence Quantificationmentioning
confidence: 99%
“…Rupp reported that a microstructure produced by sandblasting and acid etching enhances the osteogenic properties of titanium . Additionally, a surface nanotopography such as TiO 2 nanotube coatings has been shown to enhance the osteogenesis owing to its positive effects on cell adhesion, orientation, differentiation, and migration . Furthermore, a recent study found that a hierarchically micro/nanotextured surface possessed a better bioactivity due to the similar dimensional scale as that of bone collagen fibrils and elasticity resembling that of bones .…”
Section: Introductionmentioning
confidence: 89%
“…13 Additionally, a surface nanotopography such as TiO 2 nanotube coatings has been shown to enhance the osteogenesis owing to its positive effects on cell adhesion, orientation, differentiation, and migration. 14,15 Furthermore, a recent study found that a hierarchically micro/ nanotextured surface possessed a better bioactivity due to the similar dimensional scale as that of bone collagen fibrils and elasticity resembling that of bones. 16 Research from Zhang has demonstrated implants with micro/nanotextured surface could promote osseointegration when implants inserted into canine femur.…”
Section: Introductionmentioning
confidence: 99%